IMPLEMENTATION OF DIFFERENTIATED LEARNING TO IMPROVE EDUCATIONAL SCIENCE AND CHARACTER LEARNING OUTCOMES OF ELEMENTARY SCHOOL STUDENTS - Ni Putu Eni Astuti; I Wayan Suastra; Ida Bagus Arnyana; I Komang Nada Kusuma (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This research is qualitative research involving 21 fourth-grade students of SD Negeri 6 Pempatan. Based on the results of interviews with the homeroom teacher for class IV, the minimum competency assessment (AKM) for students' literacy and numeracy requires special interference, so student learning outcomes are very low, especially in science subjects. This study aims to improve student learning outcomes in science subject matter of plant body parts. This study uses differentiated learning involving three learning styles, namely visual, auditory, and kinesthetic. Methods of data collection using observation and interviews. Data analysis method with qualitative descriptive analysis. The results of this study show that the learning outcomes of fourth-grade students at SD Negeri 6 Pempatan have increased. This is evidenced by the increase in learning outcomes between learning 1 and learning 2. In addition, the findings in this study state that student-focused learning activities can improve aspects of the process of how students learn which will have meaningful learning experiences so that at this stage students can develop values from science learning and Pancasila student profiles as a form of strengthening character education.